Relationship between Family Functioning and Adolescent Depression: A Mediating Role of Self-Esteem and Peer Relationships - Iqra; Rana Zeeshan Ahmad; Dr. Amna Sarwar; Dr. Bilal Shafqat; Maham Fatima; Nusrat Jabeen (Research Journal of Psychology, 2025)
The purpose of this research analysis was to investigate adolescent depression connections to family functioning along with investigating how self-esteem and peer relationship influence these relationships. A data collection process was done from equal numbers of male and female adolescents. The research data collection took place in schools and colleges of Pakistan’s 4th and 9th populous cities Rawalpindi and Islamabad. The Family APGAR index controls family functioning while the Rosenberg self-esteem scale and Peer relationship scale for children and adolescent and 11 items Kutcher adolescent depression scale (KADS-11) are the data collection instruments applied to the chosen sample. This study followed a quantitative and correlational pattern so convenience sampling techniques were appropriate. The study results revealed minimal relationship between family functioning and adolescent depression. The evaluation showed self-esteem created a powerful indirect association between family functioning and adolescent depression ratings. The research results demonstrate that self-esteem serves as a partial mediator which links peer relationships to adolescent depression. The study results demonstrate how family interactions matter while self-esteem combined with peer emotional backing determines adolescent mental health status.